Single and combined use of the platelet-lymphocyte ratio, neutrophil-lymphocyte ratio, and systemic immune-inflammation index in gastric cancer diagnosis - Zhang, Jingliang; Zhang, Li; Duan, Shusheng; Li, Zhi; Li, Guodong; Yu, Haiyan (Frontiers in Oncology, 2023)
Platelet-lymphocyte ratio (PLR), neutrophil-lymphocyte ratio (NLR), and systemic immune-inflammation index (SII) are markers for the responses of systemic inflammation and have been shown by numerous studies to correlate with the prognosis of gastric cancer (GC). However, the diagnostic value of these three markers in GC is unclear, and no research has assessed the diagnostic value of combining PLR, NLR, and SII. This study investigated the value of PLR, NLR, and SII individually or in combination in the diagnosis of GC and elucidated the connection of PLR, NLR, and SII with the clinicopathological features of GC. This study was conducted on 125 patients diagnosed with GC and 125 healthy individuals, and subsequently PLR, NLR, and SII were calculated. The results show that PLR, NLR, and SII of the GC group were considerably higher than that of the healthy group (all p < 0.001); moreover, all three parameters were notably higher in early GC patients (stage I/II) than in the healthy population. The diagnostic value of each index for GC was analyzed using the receiver operating characteristic (ROC) curve analysis. The diagnostic efficacy of SII alone (AUC,0.831; 95% confidence interval [CI],0.777–0.885) was expressively better than that of NLR (AUC,0.821; 95% CI:0.769–0.873, p = 0.017) and PLR (AUC,0.783; 95% CI,0.726–0.840; p = 0.020). The AUC of the combination of PLR, NLR, and SII (AUC,0.843; 95% CI,0.791–0.885) was significantly higher than that of SII (p < 0.001), NLR (p = 0.017), and PLR (p = 0.020) individually. The optimal cutoff values were determined for PLR, NLR, and SII utilizing ROC analysis (SII, 438.7; NLR,2.1; PLR,139.5). On top of that, the levels of PLR, NLR, and SII were all meaningfully connected with the size of the tumor, TNM stage, lymph node metastasis, and serosa invasion (all p < 0.05). The elevated levels of NLR and SII were linked to distant metastasis (all p < 0.001). Preoperative PLR, NLR, and SII could thus be utilized as diagnostic markers for GC or even early GC. Among the three indicators, SII had the best diagnostic efficacy for GC, and the combination of the three could improve diagnostic efficiency.